Pengembangan TARM sebagai Website Pembelajaran Matematika dengan Menggunakan Flipped-classroom Learning - Maulana, Ahmad Rizqi; Manoy, Janet Trineke (Universitas Negeri Surabaya, 2025)
Based on Bappenas's goal to enhance human resource competitiveness, teachers are expected to train students in technology mastery, work ethics, attitudes, innovation, and creativity. To address this challenge, accessible technology and new strategies are needed to allow teachers more time to develop students' competencies. This research aims to develop the TARM website using the flipped-classroom learning concept, evaluated based on validity, practicality, and effectiveness criteria. The development process follows the ADDIE model. Based on the analysis results, the curriculum used is the